Experimental determination and modelling of the diesel oxidation catalysts ageing effects. (October 2019) - Guardiola, Carlos; Pla, Benjamin; Mora Pérez, Javier; Lefebvre, Damien
After-treatment systems are necessary to respect the pollutant emissions thresholds specified by regulations. However, due to system ageing, the efficiency of the after-treatment system may decrease and affect the vehicle emissions during real driving conditions. To address this issue, the model presented in this article is based on the on-engine tests performed to a set of diesel oxidation catalysts with different ageing levels, through which the ageing process is characterized. Then, the model is able to simulate the light-off temperature and slip increase due to ageing, and it is applied to a Worldwide Harmonized Light Vehicles Test Cycle for a new and a thermally aged catalysts.